Desarrollo de una propuesta para la tecnificación del proceso de obtención de aceite de coco para la empresa Amanos Artesanal (2018)
The degree project was developed along seven main chapters were made based on the development of the objectives proposed in the work of degree, managing to create a new production alternative to improve the situation of the company. It must be taken into account that chapter two responds to the first specific objective, chapters three and four cover the solution of the second specific objective; and chapter five answers the third specific objective.